Development of exchange lists for Mediterranean and Healthy Eating Diets: implementation in an intervention trial. Issue 5 (20th September 2013) - Sidahmed, E.; Cornellier, M. L.; Ren, J.; Askew, L. M.; Li, Y.; Talaat, N.; Rapai, M. S.; Ruffin, M. T.; Turgeon, D. K.; Brenner, D.; Sen, A.; Djuric, Z.
Abstract Background There has been little research published on the adaptation of diabetic exchange list diet approaches for the design of intervention diets in health research despite their clinical utility. The exchange list approach can provide clear and precise guidance on multiple dietary changes simultaneously. The present study aimed to develop exchange list diets for Mediterranean and Healthy Eating, and to evaluate adherence, dietary intakes and markers of health risks with each counselling approach in 120 subjects at increased risk for developing colon cancer. Methods A randomised clinical trial was implemented in the USA involving telephone counselling. The Mediterranean diet had 10 dietary goals targeting increases in mono‐unsaturated fats, n‐3 fats, whole grains and the amount and variety of fruits and vegetables. The Healthy Eating diet had five dietary goals that were based on the US Healthy People 2010 recommendations. Results Dietary compliance was similar in both diet arms, with 82–88% of goals being met at 6 months, although subjects took more time to achieve the Mediterranean goals than the Healthy Eating goals. The relatively modest fruit and vegetable goals in the Healthy Eating arm were exceeded, resulting in fruit and vegetable intakes of approximately eight servings per day in each arm after 6 months. A significant (P < 0.05) weight loss and a decrease in serum C‐reactive protein concentrations were observed in the overweight/obese subgroup of subjects in the Mediterranean arm in the absence of weight loss goals. Conclusions Counselling for the Mediterranean diet may be useful for both improving diet quality and for achieving a modest weight loss in overweight or obese individuals.